Problems of Hybrid Contracts in Sharia Buy Now Pay Later from the Perspective of Maqashid Syariah - Rini Putri; Insanul Nabil; Kesy Yumaida Kasih; Khalid Wiqiyan; Aidil Alfin (Al-Muamalat: Journal of Islamic Economics Law, 2026)
ENGLISH The development of the contemporary Islamic financial industry has encouraged the emergence of various innovative products based on hybrid contracts or multi-contracts as an adaptation to the needs of modern economic transactions. However, the implementation of hybrid contracts in Islamic financial institutions raises various problems in Islamic jurisprudence (fiqh muamalah), particularly related to the potential for gharar (gharar), the principle of ribawiyah (ribawiyah), the ambiguity of contracts, and the issue of Sharia compliance in modern transaction practices. This study aims to analyze the problems of hybrid contracts in Sharia Buy Now Pay Later (BNPL) services through the perspective of maqasid sharia and sharia compliance. The study used a qualitative method with a normative-legal research approach through a literature review of scientific literature, fatwas from the National Sharia Council (DSN-MUI), Sharia fintech regulations, and journals related to hybrid contracts. The results show that the implementation of hybrid contracts in Sharia BNPL provides flexibility in digital transactions, but also raises the problem of legal formalism, namely the dominance of formal compliance with contracts over the substance of maqasid sharia. Combining multiple contracts in a single transaction has the potential to create usury, imbalanced risk distribution, and unclear transactions that approach gharar. This research confirms that the formal legality of contracts does not always reflect the achievement of the principles of justice and welfare in Islamic economics, necessitating strengthened sharia oversight of digital Islamic fintech products. Therefore, strengthening contract transparency, sharia compliance, and oversight of multi-contract implementation are necessary to ensure they remain aligned with the principles of justice and welfare in Islamic economics. INDONESIA Perkembangan industri keuangan syariah kontemporer mendorong lahirnya berbagai inovasi produk berbasis hybrid contract atau multiakad sebagai bentuk penyesuaian terhadap kebutuhan transaksi ekonomi modern. Namun, implementasi hybrid contract dalam lembaga keuangan syariah menimbulkan berbagai problematika fikih muamalah, terutama terkait potensi gharar, hilah ribawiyah, ketidakjelasan akad, serta persoalan kepatuhan syariah dalam praktik transaksi modern. Penelitian ini bertujuan menganalisis problematika hybrid contract dalam layanan Sharia Buy Now Pay Later (BNPL) melalui perspektif maqashid syariah dan sharia compliance. Penelitian menggunakan metode kualitatif dengan pendekatan normative-legal research melalui studi kepustakaan terhadap literatur ilmiah, fatwa DSN-MUI, regulasi fintech syariah, serta jurnal terkait hybrid contract. Hasil penelitian menunjukkan bahwa implementasi hybrid contract dalam BNPL syariah memberikan fleksibilitas transaksi digital, namun juga memunculkan problem legal formalism, yaitu dominasi kepatuhan formal akad dibanding substansi maqashid syariah. Penggabungan beberapa akad dalam satu transaksi berpotensi melahirkan hiyal ribawiyah, ketidakseimbangan distribusi risiko, serta ketidakjelasan transaksi yang mendekati unsur gharar. Penelitian ini menegaskan bahwa legalitas formal akad tidak selalu mencerminkan tercapainya prinsip keadilan dan kemaslahatan dalam ekonomi Islam, sehingga diperlukan penguatan pengawasan syariah terhadap produk fintech syariah digital. Oleh karena itu, diperlukan penguatan transparansi akad, kepatuhan syariah, dan pengawasan terhadap implementasi multiakad agar tetap selaras dengan prinsip keadilan dan kemaslahatan dalam ekonomi Islam